Gringo Entrepreneurship in Latin America. The Thorndikes of Peru, 1901-1938 - David Wong Cam; Harold Hernández Lefranc; José Manuel Carrasco Weston (Journal of Evolutionary Studies in Business, 2018)
This article studies with a business history framework the history of immigrant entrepreneurship of a North American family in Peru, whose origin goes back to the second half of the nineteenth century and its development takes place in the first forty years of the twentieth century. The origins go back to Ernesto Thorndike, a North American businessman whose business trajectory was situated principally in Peru. At the end of his life, he saw the decline of his fortune despite his social and intellectual capital, of being part of the economic and social elite of Lima at the end of the nineteenth century and the beginnings of the twentieth, and of the diversification of its businesses. The article analyzes this evolution and indicates driving factors of success and decline: intellectual capital un-exploitable because of Peru´s political and economic instability (the construction of railroads was paralyzed at the end of nineteenth century); the lack of speed to produce the necessary tacit technical knowledge to diversify of its businesses; and the lack of bonding social capital, which prevented the constitution of a family business group that capitalized contacts and relationships that extends in time the existence of firms beyond a generation.